THE EFFECT OF VISIONER LEADERSHIP, AND LEARNING INNOVATION ON TEACHER PERFORMANCE ALIYAH STATE MADRASAH MEDAN CITY-INDONESIA - Said Ashlan; HAMBALI HAMBALI (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2022)
The reason for this research is to find out and analyze: (1) the effect of visionary leadership on teacher performance, and (2) the effect of learning innovation on teacher performance. The research subjects were the teachers of the Madrasah Aliyah Negeri Medan City with a total sample of 182 people taken by means of stratified proportional random sampling, the data were analyzed using path analysis after calculating the correlation of all research variables in the form of a matrix. The results of the analysis of the effect of exogenous variables on endogenous variables in each substructure obtained (1) visionary leadership has a positive effect on teacher performance by 5.2% (2) learning innovation behavior has a positive effect on teacher performance by 3.1%. The results of the study illustrate that (1) there is a positive direct influence of visionary leadership on teacher performance by 5.2%, and (2) there is a direct positive influence of learning innovation on teacher performance of 3.1%